Design and Implementation of Portable Signal Generator using AVR and Android App (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The signal generator which is used in all engineering, mechanical, experimental courses and other fields has high stability and large precision. The main aim of the project is to style a conveyable signal generator for faculty labs and test laboratories to get the fundamental signals like the Sne, Square, Triangle, PWM waveforms, supported wireless technology and bluetooth to speak between microcontroller and android device to line the signal parameters from android mobile. Any Android device can act as a communicable device. The result of this work can execute all the waveforms like sine, square, Triangle, and PWM within 0.1HZ to 1MHZ in accurate manner and which could be then applied to all output devices like motor, light etc,. and therefore the signal will be monitored using digital signal oscillator (DSO) or CRO and Logical analyzer